Effectiveness of Self-Care Intervention Program on Patients with Colostomy - Noor Hussein Atta, Souad Jassim Mohammed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The function of the colostomy nurse has advanced from that of a bedside caregiver to that of an enter-stomal therapist or a nurse scientific expert with ostomy care experience. Nurses play a critical role in health education, assisting and motivating patients to take care of themselves. They serve as health educators in practically all health-care settings, promoting patient health literacy and assisting them in managing and becoming acquainted with their situation. (1). Methodology: In order to fulfill the study’s aims, the researcher constructed a questionnaire format to evaluate the effectiveness of a self-care Intervention Program on patients with colostomies at Al Nasiriyah teaching hospital. The questionnaire is divided into three sections: Part I: Self-administered sheet relating to the patients’ demographic characteristics, such as (age, gender, and Marital status, educational level, and occupation). Part II: Self-Administered Sheet Concerning Patients’ Colostomy Knowledge There are twelve multiple choice questions in all. Part III: Ostomy Self-Care Observational Checklist has sixteen items. The instrument’s reliability was verified by using intra examiner (test and retest) and inter examiner (alpha Cronbach) tests, and the instrument’s validity was assessed by a panel of (15) experts. The data was analyzed using descriptive statistical data (frequency, percent, Mean of Score (MS), Variations among both pre / post Mean of Score, Standard Deviation (SD), and (RS percent) Relative Sufficiency) as well as inferential analysis (Chi-Square test, Contingency Coefficients (C.C.) test, t-test, and (ANOVA) Analysis of Covariance). Results of the study: The study’s findings revealed that the effectiveness of a self-care intervention program on patients’ colostomy knowledge and practices significantly improved. It also demonstrates that there are very significantly different in the study group’s overall primary domains connected to knowledge of patients’ and their practices between pre and post-tests. Conclusion: This study found that patients with colostomies had insufficient knowledge and suboptimal colostomy self-care practices prior to the adoption of the self-care intervention program. Their knowledge and practices improved following the introduction of the self-care intervention program. Recommendations: The study recommended that patients with colostomies receive close care via consultations and telephone conversations to assist identify and resolve their difficulties. Develop instructional special units in surgical departments, particularly in colon operations, with experienced enterstomal caregivers and all essential reference resources, such as technical manuals and multimedia elements.